2018
DOI: 10.1007/s11356-018-1847-z
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the dust deposition on solar photovoltaic modules

Abstract: Solid particles impair the performance of the photovoltaic (PV) modules. This results in power losses which lower the efficiency of the system as well as the increases of temperature which additionally decreases the performance and lifetime. The deposited dust chemical composition, concentration and formation of a dust layer on the PV surface differ significantly in reference to time and location. In this study, an evaluation of dust deposition on the PV front cover glass during the non-heating season in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 29 publications
(30 reference statements)
0
32
0
1
Order By: Relevance
“…The prices for grid energy based on prices for 2017 in Poland for energy purchases 0.146 €/kWh, energy sell 0.117 €/kWh. The CO2 emission for electrical grid system energy is 0.867 kg/kWh [12].…”
Section: Experimental Data and System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prices for grid energy based on prices for 2017 in Poland for energy purchases 0.146 €/kWh, energy sell 0.117 €/kWh. The CO2 emission for electrical grid system energy is 0.867 kg/kWh [12].…”
Section: Experimental Data and System Descriptionmentioning
confidence: 99%
“…The results estimate the cost for 1 kWh of electrical energy by about $0.51 and the average of CO2 emissions avoidance by about 1840 kg/year compared with conventionally used in that site. The energy degradation due to the natural dust deposition on the PV module was studied by Jaszczur et al [11] and Styszko et al [12]. They estimated time characteristics of dust deposition distribution as well as its influence on energy production and efficiency loss.…”
Section: Introductionmentioning
confidence: 99%
“…The deposited dust particles were removed using deionised water and a scratcher with suction pump [13]. The water with dust was collected in plastic containers, followed by freeze-drying (Liophilizator Alpha 1-4 LD).…”
Section: Experimental and Numerical Set-upmentioning
confidence: 99%
“…The natural dust deposition on the PV modules front cover glass was experimentally analysed in [13] by means of several PV modules during exposure periods from 1 day up to 1 week. The results showed that dust deposition intensity on the module surface ranged from 7.5 to 42.1 mg/m 2 for exposure periods of one day while the measured dust deposition for one week ranged from 25.8 to 277.0 mg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In all the PV module types, when the cell temperature increases, the energy conversion efficiency significantly decreases [6]. Additionally, accumulative dust deposition on the module front cover surface reduces the incident solar radiation intensity and further reduces the power output [7]. In recent years a number of research studies were performed, reporting in a separate manner the impact of the dust or temperature on PV efficiency .…”
Section: Introductionmentioning
confidence: 99%